2019
DOI: 10.1016/j.arr.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The prion-like spreading of α-synuclein: From in vitro to in vivo models of Parkinson’s disease

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease.PD is characterized by the loss of dopaminergic neurons, primarily in brain regions that control motor functions, thereby leading to motor impairments in the patients. Pathological aggregated forms of the synaptic protein, α-synuclein (α-syn), are involved in the generation and progression of PD. In PD brains, αsyn accumulates inside neurons and propagates from cell-to-cell in a prion-like manner. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 137 publications
(261 reference statements)
5
60
0
Order By: Relevance
“…Previous studies have shown that α-syn can spread across brain regions [47][48][49]. Our study showed that hα-syn (A53T) expressed in SNc neurons can arrive at distant cerebral regions along projecting fibers.…”
Section: Neural Plasticitysupporting
confidence: 55%
“…Previous studies have shown that α-syn can spread across brain regions [47][48][49]. Our study showed that hα-syn (A53T) expressed in SNc neurons can arrive at distant cerebral regions along projecting fibers.…”
Section: Neural Plasticitysupporting
confidence: 55%
“…The extracellular secretion of key proteins implicated in neurodegenerative diseases, including α-synuclein, tau, and prion, via both exosomal and nonvesicular pathways has been reported [18,41,42,52]. Such secretion through dual pathways would accelerate their spread.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 This notwithstanding, both oligomers and fibrils have been found to induce neuronal cell death, [6][7][8] and can mediate the dissemination of α-syn pathology, although fibrils are considered the most prone to trigger the prion-like spreading. 6,[8][9][10][11] This evidence supports that as α-syn deposition plays a central role in the onset of several neurodegenerative disorders, reducing α-syn levels, oligomer formation, fibrillation, or cell-to-cell transmission, may all represent useful strategies to contrast/slow down the synucleinopathies, which still nowadays can only be managed by symptomatic therapies.…”
Section: Introductionmentioning
confidence: 60%
“…Since α‐syn is intrinsically disordered and does not own a defined tertiary structure in solution, while displaying different conformations depending on the surrounding environment (partially α‐helical and oligomeric species), it is also difficult to predict which are most relevant functional forms of the protein . This notwithstanding, both oligomers and fibrils have been found to induce neuronal cell death, and can mediate the dissemination of α‐syn pathology, although fibrils are considered the most prone to trigger the prion‐like spreading …”
Section: Introductionmentioning
confidence: 99%